(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2017)
The issue of maintenance and the enforcement of Maintenance Orders issued by the syariah courts have often been the subject of complaint, especially among women after divorce. Arguably,Family Law does have detailed provisions regarding maintenance,however there are still significant shortcomings in the enforcement of the maintenance orders, especially when the former husband or father who has been instructed to pay maintenance fails to cooperate or is negligent. This paper aims to review the effectiveness of the Family Support Division in performing its functions and highlight the difficulties encountered in the effort to resolve problems relating to enforcement of the orders, particularly for maintenance of children after divorce. In addition, this paper also touches upon the practice in dealing with this issue by some developed countries as a means of comparison to improve the performance of the Family Support Division. Keywords: child maintenance,syariah courts, Family Support Division, enforcement, developed countries